2022
DOI: 10.3389/fendo.2022.931573
|View full text |Cite
|
Sign up to set email alerts
|

GPCR heteromers: An overview of their classification, function and physiological relevance

Abstract: G protein-coupled receptors (GPCRs) are capable of interacting to form higher order structures such as homomers and heteromers. Heteromerisation in particular has implications for receptor function, with research showing receptors can attain unique expression, ligand binding, signalling and intracellular trafficking upon heteromerisation. As such, GPCR heteromers represent novel drug targets with extensive therapeutic potential. Changes to ligand affinity, efficacy and G protein coupling have all been describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…Additionally, in that both receptors stimulate the CWI pathway, the interdependence could be consistent with a requirement for the formation of a peroxidase-stimulated heterodimer complex between Fg Ste2 and Fg Ste3 in the cell membrane. GPCR dimers (hetero and homo), as well as higher order oligomers, are well-documented to play important roles in modifying GPCR signal transduction ( 69 ), including a prior report of Ste2p homooligomerization in yeast mating ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in that both receptors stimulate the CWI pathway, the interdependence could be consistent with a requirement for the formation of a peroxidase-stimulated heterodimer complex between Fg Ste2 and Fg Ste3 in the cell membrane. GPCR dimers (hetero and homo), as well as higher order oligomers, are well-documented to play important roles in modifying GPCR signal transduction ( 69 ), including a prior report of Ste2p homooligomerization in yeast mating ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple previous studies have shown that incretin receptors can form heterodimers, as demonstrated, for example, using bioluminescence resonance energy transfer (BRET) (Schelshorn et al, 2012;Whitaker et al, 2012;Dale et al, 2022). In particular (Roed et al, 2015), have shown that both the GIPR and the GCGR form heteromers with the GLP-1R when expressed in HEK-293 cells.…”
Section: Functional Interactions Of Incretin Receptors With Other Gpcrsmentioning
confidence: 97%
“…A Post-translational modifications (PMTs): sites of O-Glycosylation (Ser6, Thr16, Ser17) [ 70 , 71 ], sulfation (Tyr3, 10, 14, 15) [ 73 , 75 78 ], palmitoylation (Cys321, 323 and 324) [ 79 91 ] and phosphorylation (Ser336, 337, 342 and 349) [ 235 , 236 ] are represented by colored circles. Factors such as G-protein coupling ( B ) [ 28 , 60 , 97 103 ], mutations ( C ) [ 126 129 , 177 , 178 ], surface density [ 117 123 ] and oligomerization [ 136 149 ] ( D ) and membrane surrounding [ 152 173 ] ( E ) are also exemplified …”
Section: Structural Variability Of Chemokines Receptors Involved In H...mentioning
confidence: 99%
“…Oligomerization of receptors —Many GPCRs are able to interact with each other to form higher-order structures (homomers and/or heteromers) (Fig. 2 D) that can, upon allosteric modulation, exhibit distinct biochemical properties from monomers [ 136 139 ]. Both CCR5 and CXCR4 have been shown to form many different homo and heteromers whose exhaustive lists can be found in [ 140 ] (Table 1) and [ 141 ] (Table 1).…”
Section: Structural Variability Of Chemokines Receptors Involved In H...mentioning
confidence: 99%